Transparansi dalam Etika Bisnis Digital: Studi Bibliometrik tentang Transaksi Online Menggunakan VOSviewer dan Tinjauan Literatur - Ismi Rojayanti; Udik Jatmiko; Dela Fitri Nurmaya; Vany Eka Putri; Anggun Catur Natalia; M. Shadam Safarudin; M. Adi Trisna Wahyudi (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
The purpose of this study is to analyze online transactions from the perspective of transparency in digital business ethics, focusing on the Shopee platform. In the digital economy era, online transactions have become increasingly important, yet issues such as fake reviews and inaccurate product information remain challenges. This study employs a qualitative approach with bibliometric methods and a literature review to analyze 30 articles from 2019 to 2024. The results indicate that while Shopee has implemented various measures to enhance integrity and openness, issues such as fake reviews and false product information persist. The study recommends improvements in information monitoring and seller education to enhance transparency and customer trust.